Influence of Cognitive CoachingSM on the Development of Self-efficacy and Competency of Principals - Rogers, Todd; Hauserman, Cal; Skytt, Jacqueline (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
The influence of Cognitive CoachingSM on the development of self-efficacy and competency was examined as part of the program evaluation of the Leader2Leader (L2L) Pilot Program for beginning principals in Alberta, Canada. Fifteen qualified principals (coaches) and 23 new principals completed the L2L Pilot Program that took place over 18 months. Self-efficacy and the acquisition of seven principal practice competencies were measured at baseline and the end of the program. The findings present a stronger case for increasing levels of professional competency than they do for increasing self-efficacy. A series of recommendations made and endorsed by the coaches and new principals for improving the process of Cognitive CoachingSM are provided